The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1432-1033.1978.tb12250.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acetylglutamate in Ureotelism

Abstract: The level of N-acetyl-L-glutamate showed a diurnal rhythm, which was associated primarily with dietary ingestion. Since the hepatic level of arginine, activator for acetylglutamate, is one of the plausible principal factors responsible for the regulation of acetylglutamate level, the effect of arginine was further studied. The intraperitoneal administration of a large amount of arginine increased the level of acetylglutamate and the effect was augmented by the combined administration of glutamine. The arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Shigesada et al (17) reported that the increase of N-acetylglutamate concentration under physiological conditions stimulated urea synthesis in isolated hepatocytes. The Ka value (0.11 mM) of the carbamylphosphate synthetase for the N-acetylglutamate was reported to be close to its physiological concentrations in mitochondria (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Shigesada et al (17) reported that the increase of N-acetylglutamate concentration under physiological conditions stimulated urea synthesis in isolated hepatocytes. The Ka value (0.11 mM) of the carbamylphosphate synthetase for the N-acetylglutamate was reported to be close to its physiological concentrations in mitochondria (14).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the N-acetylglutamate concentration has correlated well with urea synthesis in intact animals (14,17,27,28) and in isolated hepatocytes (12,29). Many investigators have indicated that a change in N-acetylglutamate synthesis was involved in regulating the liver concentration of N-acetylglutamate (17,26). N-Acetylglutamate synthetase (EC 2.3.1.1) has been shown to catalyze the acetylCoA-dependent acetylation of glutamate in liver mitochondria (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were killed 8 h after the start of the feeding and acetylglutamate synthetase was purilied as described in the text [27], ammonia [19,20], intramitochondrial ATP/ ADP ratio [28] and Ca2+ [29], is a mediator which regulates urea biosynthesis in mammalian liver. The intramitochondrial level of acetylglutamate is regulated by the rate of its synthesis [3,7] and by the rate of the degradation [30]. Factors known to regulate the synthesis of acetylglutamate are the intracellular levels of arginine and glutamate [6] and the amount of acetylglutamate synthetase [9].…”
Section: ) Und O F J D Mice ( B )mentioning
confidence: 99%